2011
DOI: 10.1186/cc10567
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ventilator setting by flow and pressure waveforms analysis during noninvasive ventilation for acute exacerbations of COPD: a multicentric randomized controlled trial

Abstract: IntroductionThe analysis of flow and pressure waveforms generated by ventilators can be useful in the optimization of patient-ventilator interactions, notably in chronic obstructive pulmonary disease (COPD) patients. To date, however, a real clinical benefit of this approach has not been proven.MethodsThe aim of the present randomized, multi-centric, controlled study was to compare optimized ventilation, driven by the analysis of flow and pressure waveforms, to standard ventilation (same physician, same initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
(23 reference statements)
0
22
0
1
Order By: Relevance
“…Having said this, we have shown that the occurrence of asynchronies is very frequent even when the settings are performed in expert centers [2]. A close look at some indirect indices of mismatching (that is, the flow waveform), may help the clinician to detect the most frequent asynchrony between the patient and the machine, that is, ineffective effort [22]. Indeed, it is of clinical interest that, despite the different underlying pathologies, the settings decided by the operators to achieve the same aims (that is, gas exchange amelioration and tidal volume increase) are very similar, and also induced comparable amounts of asynchronies.…”
Section: Discussionmentioning
confidence: 99%
“…Having said this, we have shown that the occurrence of asynchronies is very frequent even when the settings are performed in expert centers [2]. A close look at some indirect indices of mismatching (that is, the flow waveform), may help the clinician to detect the most frequent asynchrony between the patient and the machine, that is, ineffective effort [22]. Indeed, it is of clinical interest that, despite the different underlying pathologies, the settings decided by the operators to achieve the same aims (that is, gas exchange amelioration and tidal volume increase) are very similar, and also induced comparable amounts of asynchronies.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-ventilator asynchrony, and therefore the likelihood of NPPV failure may be prevented by the optimisation of ventilator settings using the screen ventilator waveforms, adjusting trigger sensitivity, increasing PEEP, minimising air leaks or using different modes or more sophisticated ventilators [109]. New modes of ventilation, such as neutrally adjusted ventilator assist, have been documented to reduce asynchrony even in the presence of air leaks [110].…”
Section: Nppv Failurementioning
confidence: 99%
“…Patients were ventilated with bi-level positive airway pressure in S/T mode (BiPAP Vision or Respironics V60). Expiratory positive airway pressure was initially set at 4 cm H 2 O and titrated according to the flow curve to ensure that expiratory flow reached zero prior to inspiration or diminished ineffective efforts [16]. FiO 2 was set to maintain SpO 2 at around 95%.…”
Section: Nppv Settingmentioning
confidence: 99%